Participación del factor transcripcional NF-kB en la endocitosis de Staphylococcus aureus en células de epitelio mamario bovino estimuladas por prolactina - Lara Zarate, Leticia (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
Bovine mastitis is considered one of the most important diseases in dairy farming worldwide. This condition is characterized by an inflammatory response of the mammary gland of multifactorial origin, mainly caused by bacterial infections. Staphylococcus aureus is the prevalent isolates pathogen most often in cases of mastitis (> 70%), it has the characteristic of being a facultative intracellular pathogen, invading epithelial cells by a mechanism of endocytosis. In a previous study it showed that the bovine prolactin (bPRL, 5 ng / ml) stimulates endocytosis of S. aureus (ATCC 27543) by bovine mammary epithelial cells (CBSS), and together with the infection, regulates elements of the response innate immune in CBSS. The expression of these elements depends on the activation of the transcription factor NF-kB, and has recently been shown to activate NF-kB bPRL factor in bovine mammary epithelium regulating the expression of proinflammatory cytokines. However, activation of this transcription factor is regulated by the PRL during the infectious process with S. aureus is itself known. Based on the above, the objective of this study was to determine the regulation of signaling pathway NF-kB during endocytosis of S. aureus in bovine mammary epithelial cells stimulated with bPRL. The results showed that the bPRL induces activation of NF-kB in the CBSS. While S. aureus inhibits nuclear translocation of this factor, even in bPRL (5 ng / ml), which promotes the endocytosis of the bacteria. Regarding the regulation of expression of elements of the innate immune response, the data showed that bPRL (5 ng / ml) induces the expression of mRNA of TNF-a, TAP, iNOS, besides NO production in the CBSS.

La mastitis bovina es considerada una de las enfermedades de mayor relevancia en la ganadería lechera a nivel mundial. Esta patología se caracteriza por una respuesta inflamatoria de la glándula mamaria de origen multifactorial, ocasionada principalmente por infecciones bacterianas. Staphylococcus aureus es el patógeno prevalente que se aísla con mayor frecuencia en casos de mastitis (> 70%), éste posee la característica de ser un patógeno facultativo intracelular, invadiendo a las células epiteliales por un mecanismo de endocitosis. En un trabajo previo se demostró que la prolactina bovina (bPRL, 5 ng/ml) estimula la endocitosis de S. aureus (ATCC 27543) por células epiteliales mamarias bovinas (CEMB), y en conjunto con la infección, regula elementos de la respuesta inmune innata en las CEMB. La expresión de estos elementos depende de la activación del factor transcripcional NF-kB, y recientemente se ha demostrado que la bPRL activa al factor NF-kB en el epitelio mamario bovino regulando la expresión de citocinas proinflamatorias. Sin embargo, se desconoce sí la activación de este factor de transcripción es regulado por la PRL durante el proceso infeccioso con S. aureus. Con base en lo anterior, el objetivo del presente trabajo fue determinar la regulación de la vía de señalización de NF-kB durante la endocitosis de S. aureus en células de epitelio mamario bovino estimuladas con bPRL. Los resultados mostraron que la bPRL induce la activación de NF-kB en las CEMB. Mientras que S. aureus inhibe la translocación nuclear de este factor, aún en presencia de bPRL (5 ng/ml), lo cual favorece la endocitosis de la bacteria. Con respecto a la regulación de la expresión de elementos de la respuesta inmune innata, los datos mostraron que la bPRL (5 ng/ml) induce la expresión de los mRNA de TNF-a, TAP, iNOS, además de la producción de NO en las CEMB.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FMVZ-M-2010-0015; Endocitosis; Staphylococcus aureus; Bovinos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1925